To assess whether the equation \( 3^{-5 \cdot (81^{1/4})^3} - 4 = 3^{-6} \) is true or false, let's break it down step by step.
-
Calculate \( 81^{1/4} \): \[ 81 = 3^4 \implies 81^{1/4} = (3^4)^{1/4} = 3^{4 \cdot \frac{1}{4}} = 3^1 = 3 \]
-
Now calculate \( (81^{1/4})^3 \): \[ (81^{1/4})^3 = 3^3 = 27 \]
-
Calculate \( -5 \cdot (81^{1/4})^3 \): \[ -5 \cdot 27 = -135 \]
-
Evaluate the expression \( 3^{-135} - 4 \): So the original left-hand side becomes \( 3^{-135} - 4 \).
-
Right-hand side is \( 3^{-6} \).
-
Compare the two sides: The left-hand side \( 3^{-135} - 4 \) clearly does not equal \( 3^{-6} \) because \( 3^{-135} \) is an extremely small number compared to \( 4 \), and certainly not equal to \( 3^{-6} \).
Given the calculations and comparisons, the statement is:
False. The numerator simplifies to \( 3^{-2} \) and \( \frac{3^{-2}}{3^{-4}} \neq 3^{-6} \).
However, the valid justification option you provided is incorrectly stating the simplification process. In this case, it's best to state that the entire left-hand side is not equal to the right-hand side based on our earlier steps, concluding the overall equation to be false.